Risk-Aversion for Negative Health Outcomes May Promote Individual Compliance to Containment Measures in Covid-19 Pandemic - Cerami, Chiara; Galandra, Caterina; Santi, Gaia Chiara; Dodich, Alessandra; Cappa, Stefano Francesco; Vecchi, Tomaso; Crespi, Chiara (Frontiers in Psychology, 2021)
First-person experience of stressful life events can change individuals’ risk attitudes, driving to increased or decreased risk perception. This shift to more risk-averse or risk-loving behaviors may find a correlate in the individual psycho-socio-emotional profile. To this purpose, we aimed to estimate the relationship between differences in risk-taking attitudes toward possible negative health outcomes and psycho-socio-emotional dimensions modulating the experience of life-threatening situations, in the context of the Covid-19 pandemic. In March 2020, we launched the PsyCovid Study (https://wprn.org/item/428452) to assess psycho-socio-emotional changes due to Covid-19 pandemic in the Italian population. Additionally, we distributed to 130 participants the Covid-19 Risk Task, including monetary and health-related stimuli, estimating a measure of risk-aversion toward health and classifying participants on the basis of their risk-attitude profiles. The set of psycho-socio-emotional variables was reduced to three PCA components: Proactivity, Isolation, Inactivity. The individual degree of risk-aversion toward negative health outcomes was directly related to Proactivity, encasing empathic, social support and positive coping strategies, which may prompt individuals to put in place self-protection strategies toward possible negative health consequences. These findings indicate that a risk-averse profile toward possible negative health outcomes may be associated to higher levels of individual prosocial and proactive dispositions, possibly making individuals’ more compliant with the social and hygienic guidelines and, thus, reducing their exposure to the SARS-CoV-2 infection.